1987
DOI: 10.1172/jci113040
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of phosphatidylinositol bisphosphate hydrolysis to calcium mobilization and functional activation in fluoride-treated neutrophils.

Abstract: Sodium fluoride (20 mM) effected rapid hydrolysis of phosphatidylinositol bisphosphate (PIP2) in human neutrophils. Intracellular free Ca2+ levels increased after PIP2 hydrolysis but before respiratory burst activation. Both the increase in intracellular free Ca2+ levels and the extent of functional activation were dependent on the availability of extracellular Ca2+. The rate of F--

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

1990
1990
2000
2000

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…This InsP3-independent action of mastoparan is relatively insensitive to 15-HETE also suppressed the PMN oxidative burst elicited with another G protein activator AIFZ (35). In contrast to mastoparan, however, the AlFZ-induced rise in [Ca2+]i is quite slow (36), and PMN responsiveness to AIF-is pertussis toxin-insensitive (37 (42). In addition, in some cells 15-HETE is preferentially incorporated into phosphatidylinositol, which yields altered species of diacylglycerol when the cells are hormonally stimulated (39).…”
Section: Discussionmentioning
confidence: 85%
“…This InsP3-independent action of mastoparan is relatively insensitive to 15-HETE also suppressed the PMN oxidative burst elicited with another G protein activator AIFZ (35). In contrast to mastoparan, however, the AlFZ-induced rise in [Ca2+]i is quite slow (36), and PMN responsiveness to AIF-is pertussis toxin-insensitive (37 (42). In addition, in some cells 15-HETE is preferentially incorporated into phosphatidylinositol, which yields altered species of diacylglycerol when the cells are hormonally stimulated (39).…”
Section: Discussionmentioning
confidence: 85%
“…Despite the absence of any putative signals prior to G-protein activation, AlF-induced an extensive and sustained increase in F-actin content in intact human neutrophils. The AlF-response was characterized by an initial lag period, similar to that preceding AlF -induced activation of the respiratory burst in human neutrophils (27,28). A reason for this lag period could be that AlF-diffuses slowly to its binding site on G proteins.…”
Section: Discussionmentioning
confidence: 97%
“…For diradylglycerol mass, this stimulus is far more potent than fMLP (including with cytochalasin B or other forms of priming), consistent with its derivation from multiple mechanisms and phospholipid pools. Regarding phospholipase C activation, English and colleagues [37] previously showed that fluoride is an extremely potent stimulus for phosphoinositide hydrolysis and inositol phosphate release. Based on ethanol inhibition, the present studies suggest that phospholipase C also acts on PC under these conditions.…”
Section: Discussion Referencesmentioning
confidence: 99%
“…In contrast to the rapid activation of superoxide by fMLP, fluoride activates after a prolonged lag (about 5 to 8 min). Previously, English and colleagues [37] demonstrated that fluoride activates the phospholipase C-dependent hydrolysis of PIP2. In addition, fluoride causes calcium mobilization [4], arachidonic acid release [31], and increased cyclic AMP levels in neutrophils [38].…”
Section: Introductionmentioning
confidence: 99%